Backed bladelet production among Magdalenian groups in south-eastern Poland - selected examples - Grużdź, Witold; Pyżewicz, Katarzyna (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2022)
In the presented article, we attempted to interpret Magdalenian backed bladelets in terms of recognizing the methods of their production. For this purpose, we studied the microblade technology, the intentional fracturing of blanks using specific procedures, including the microburin technique, and retouching. We applied typological, morphometrical, and morphological studies. We based our conclusions on the results of technological studies of 154 artefacts – backed bladelets and microburins, coming from three sites – Ćmielów 95 “Mały Gawroniec”, Podgrodzie 16, and Maszycka Cave. As a result, we obtained preliminary data on the final stages of the chaîne opératoire in the production of backed bladelets.
il. ; 25 cm
Keywords: backed bladelets; lithic technology; microburin technique; Magdalenian; south-eastern Poland; morphometric analysis